2017
DOI: 10.11606/s1518-8787.2017051000053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of inadequate medicine home storage: a community-based study

Abstract: OBJECTIVE Assess the extent of inadequate home storage of medicines andidentify important risk factors.METHODS A cross-sectional survey based on a probability sample in the community, conducted in 267 households in Cuité, State of Paraíba, Northeast Brazil, in 2014. Logistic regression was used to study the risk factors.RESULTS The prevalence of households with inadequate storage was 76.0%. Problems with storage include direct exposure to sunlight in 10.9% of households, the presence of dust in 23.6%, and stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 22 publications
5
25
2
4
Order By: Relevance
“…Our study found that 24% of households had expired paracetamol products. This is a lower rate than the two-thirds of households found in a recent Belgian study [44], and higher than PLOS ONE the 2.4% found in a Brazilian study [45]. Initiatives such as 'Disposal of Unwanted Medication Properly (DUMP)' previously done in New Zealand [46] or 'Return Unwanted Medicines (RUM)' in Australia [35] where people had an easy, simple means of returning unnecessary medicines to the pharmacy could assist in reducing such expired stock being accumulated in households.…”
Section: Plos Onecontrasting
confidence: 65%
“…Our study found that 24% of households had expired paracetamol products. This is a lower rate than the two-thirds of households found in a recent Belgian study [44], and higher than PLOS ONE the 2.4% found in a Brazilian study [45]. Initiatives such as 'Disposal of Unwanted Medication Properly (DUMP)' previously done in New Zealand [46] or 'Return Unwanted Medicines (RUM)' in Australia [35] where people had an easy, simple means of returning unnecessary medicines to the pharmacy could assist in reducing such expired stock being accumulated in households.…”
Section: Plos Onecontrasting
confidence: 65%
“…Notwithstanding the higher rate of in-home storage among women [19,58], the lower wastage rate was linked to households whose stored medicines were organized by female subjects [15]. Other studies have con rmed high storage rates among women [15,95,96] with some reasons such as; gender-related physiopathology, lifestyle, contact to the health system and other biological differences such as pregnancy [96,97]. However other variations such as; women's tendency to excessive purchase and self-medication, lacks medical reasoning and can potentially be the focal point for improvement [98].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 22 studies, six [15,55,57,[65][66][67] addressed the disposal practice among households. The most commonly used method of medicine disposal was throwing them in the garbage.…”
Section: Conditions Of Storagementioning
confidence: 99%
See 2 more Smart Citations